Selenium addition to green papaya extract improves epidermal wound healing - Rahman, Mohammad Tariqur; Akram, Haris B.; Bero, Dinie Najwa; Mohamad, Mohd Yusuf (2010)
Introduction: Wounds due to injuries for various reasons and for the diabetic patients have been a major public health concern. In the search for a wound healing agent of herbal origin, we have earlier reported the efficiency of the green (unripe) Carica papaya extracts [Food Chem Toxicol. 2008. 46: 2384-2389]. Here we report that addition of Se with green papaya extract results in further improvement of wound healing efficiency. Results: During the first phase (0-4 days) of healing of epidermal wound (induced by biopsy puncture on mouse epidermis, 5 mm in diameter) use of the water extract (WE) without Zn or Se results in maximum reduction, i.e., ~70% of the initial wound area by day 2. However, 14 days are required for the complete healing. Average shortest time (day) taken for the complete healing was observed using the PBS extract (PE) with Se at 0.5 or 1.0 mg/g of the extract. Most efficient healing, as calculated by comparing total time required for healing with or without extracts, was observed with Se addition with the PE or WE. Notably, unlike the water extract, the PBS extract does not contain any tannin while it contains more protein than water extract. However, total yield, as measured by extract (mg)/papaya flesh (100g), is comparable for both PBS and water extracts. Conclusions: Green papaya extract prepared in PBS if added with appropriate amount of Se can be used as a potential natural source of wound healing which at the same time will be safer than synthetic drugs.